Knowledge Attitude and Practices regarding COVID-19 among Nurses Working in Teaching Hospital, Pokhara, Nepal - Shrestha, Kalpana; Pokhrel, Ganga; Singh, Sakun; Shrestha, Chandan (Journal of Karnali Academy of Health Sciences, 2021)
Background: Coronavirus disease 2019 (COVID-19) is a highly infectious respiratory disease that has affected 216 countries globally. In this pandemic, nurses are in the frontline in catering infected patients. Protection of health care providers and prevention of intra-hospital transmission are important aspects in epidemic response that requires updated knowledge, positive attitude and good practices among health care providers. Therefore, the aim of the study was to identify the knowledge, attitude and practices among nurses towards COVID-19. Methods: Quantitative, cross sectional research design was used to conduct the study among 120 nurses in Manipal Teaching Hospital, Pokhara. Probability- simple random sampling was done and self-administered questionnaire was used for data collection from 29th May to 12th June. Descriptive and inferential statistics such as frequency, percentage, mean, standard deviation, t-test, ANOVA and Karl Pearson coefficient of correlation test were used to analyze the data using IBM SPSS Version 20. Results: The mean knowledge, attitude and practice score were 14.05±3.74, 30.56±3.72 and 7±1.59 respectively. Less than half (47.5% and 43.3% respectively) had good knowledge and practice and 50.8% had positive attitude towards COVID-19. Statistically significant differences were observed in working department in regard to knowledge (p<0.001). Positive correlation was observed in attitude and practice score (p= 0.001). Conclusions: Majority of the nurses had good to moderate knowledge. However, practice was poor and only half of the nurses had positive attitude towards COVID-19. The study emphasizes the greater need of motivation and reassurance to promote positive attitude that may eventually lead to safe practices.